Carbapenem-Resistant but Cephalosporin-Susceptible Pseudomonas aeruginosa in Urinary Tract Infections: Opportunity for Colistin Sparing - Márió Gajdács (MDPI AG, 2020)
This paper briefly reports the occurrence and epidemiology of carbapenem-resistant but cephalosporin-susceptible (Car-R/Ceph-S) Pseudomonas aeruginosa isolates from urinary tract infections (UTIs) in a tertiary-care hospital in the Southern Region of Hungary, and the phenotypic characterization of the possible resistance mechanisms in these isolates. Isolates and data were collected regarding P. aeruginosa UTIs corresponding to the period between 2008 and 2017. Susceptibility testing was performed using the Kirby-Bauer disk diffusion method; minimum inhibitory concentrations (MICs) of the isolates were determined using E-tests. The phenotypic detection of ampicillin C-type (AmpC) β-lactamases, efflux pump overexpression and carbapenemase production was also performed. P. aeruginosa represented n = 575 (2.72% ± 0.64%) from outpatient, and n = 1045 (5.43% ± 0.81%) from inpatient urinary samples, respectively. Based on the disk diffusion test, n = 359 (22.16%) were carbapenem-resistant; in addition to carbapenems, n = (64.34%) were also resistant to ciprofloxacin; n = (60.17%) to gentamicin/tobramycin; n = (58.51%) to levofloxacin; and n = (27.57%) to amikacin. From among the carbapenem-resistant isolates, n = 56 (15.59%) isolates were multidrug-resistant, while n = 16 (4.46%) were extensively drug-resistant. From among the Car-R/Ceph-S isolates (n = 57), overexpression of AmpC was observed in n = 7 cases (12.28%); carbapenemase production in n = 4 (7.02%); while overexpression of efflux pumps was present in n = 31 (54.39%) isolates. To spare last-resort agents, e.g., colistin, the use of broad-spectrum cephalosporins or safe, alternative agents should be considered in these infections.